EMPOWERMENT OF BUREAUCRACY IN THE FINANCIAL MANAGEMENT AGENCY AND REGIONAL PROPERTY NORTH SULAWESI PROVINCE - Fernando Noubel Waleleng; Wilson Bogar; Charles H.S Tangkau; stanny sicilia rawung (STIE AMKOP, 2019)
Research purpose is to describe empowerment of bureaucracy on the Financial Management Agency and Regional Property of North Sulawesi Province and determinants. Research method used qualitative approach with data collection technique is observation, interview, and documentation. Primary data source is Informants set through purposive technique. Data analysis Technique using steps namely: data reduction, data display, and Verification and Conclusion. Results of research show that (1) Empowerment Bureaucracy through Strengthening Human Resources at Financial Management Agency and Regional Property of North Sulawesi Province carried out with various effort as special training and general training, advanced formal education , and directives in the meeting forum with staff , (2) Empowerment bureaucracy through strengthening culture do with mean for change mind set and culture work (culture-set) bureaucrats who haven't fully support bureaucracy that is efficient, effective , productive , and professional , (3) Factors determinant Empowerment Financial Management Agency and Regional Property of North Sulawesi Province is institution commitment factor to organize its empowerment programs and institution attitude factor ( leader ) looks at urgency of bureaucracy empowerment program.